Assessing the risk of developing type 2 diabetes mellitus among medical students in Chennai using Indian diabetes risk score - S., Gopalakrishnan; R., Rama; M., Muthulakshmi (International Journal Of Community Medicine And Public Health, 2017)
Background: Prevalence of type 2 diabetes mellitus [T2DM] is becoming alarmingly high among younger age groups impacting on their physical, mental, social and academic wellbeing and therefore warrants early detection and prevention. The Indian diabetes risk score [IDRS] is an efficient screening tool to detect the high risk individuals at an early stage. Objective of this study is to assess the level of risk of developing T2DM among medical students using the IDRS. Methods: This cross sectional study was done using the MDRF-IDR Score to identify the ‘at risk’ medical students. Simple random sampling was used and data collected from among the 251 willing students. Their risk score was calculated using a structured questionnaire. Data was analysed using SPSS Ver.15 software. Results: This study shows that about 57.4% are moderately at risk and 2% are at high risk for developing diabetes mellitus. About 86.1% medical students belonged to nuclear family, 42.6% had family history of diabetes mellitus, 76.5% carried out moderate physical activity and 50.2% were overweight / obese. Family history of diabetes, lack of physical activity and overweight / obesity were found to be potential risk factors for developing diabetes mellitus (p<0.0001). Conclusions: This study reveals that in the existing urban lifestyle, adolescents and youths are highly vulnerable to diabetes mellitus. Primordial and primary prevention are the most effective preventive measure and therefore, appropriate and stringent lifestyle modifications need to be implemented in order to minimize the risk of developing the disease later in life.